AB0825-HPR "It's like a juggling act": ra patients experience a life of 'fluctuating balances'. (23rd January 2014) - Flurey, C. A.; Morris, M.; Pollock, J.; Hughes, R.; Richards, P.; Hewlett, S.
Abstract : Background: Life with RA has been described as unpredictable and full of uncertainty. However, this issue has not previously been explored in depth on current, more aggressive treatment regimes. Objectives: The aim of this research was to produce an explanatory model of how RA patients experience both daily life and flare Methods: Study 1: Semi-structured interviews to discuss the experience of daily life and flare with RA. These data were analysed using Thematic Analysis. Study 2: Q-Methodology: A different set of RA patients sorted 39 statements about daily life with RA and 23 statements about their motivations for seeking help for their RA flares (generated by the Study 1 interviews) across a forced distribution, in ranked order of agreement. Data were analysed using centroid factor analysis with varimax rotation (i.e. the participants and not the items are the variables). Demographic and clinical data were collected and patients completed comments booklets about their rationale for sorting the statements. The findings from these two studies were combined to produce an explanatory model of RA patients' experiences of daily life and flare. Results: Study 1: 15 patients: 12 female, mean age 51yrs (SD 11.8), dis dur 14.8yrs (SD 8.6), HAQ 1.3 (SD 1.0) Study 2: 30 patients: 22 female, mean age 56yrs (SD 24.0), dis dur 13.2 (SD 8.6), HAQ 1.4 (SD 1.7). Overall findings: Patients experience a life of fluctuating balances with RA, in which they are constantly trying to maintain an optimum balance on a continuum of 'Living with RA in the background', 'RA moving into the foreground' and 'Dealing with RA in the foreground'. Living with RA in the background: Involves patients mediating both the physical and emotional impact of RA on their lives: "it's not going to get the better of me" and redefining their identity to incorporate their RA: "you just accept it as normal" . RA moving into the foreground: Characterised by unwelcome reminders of RA due to its unpredictable nature: "I never know what I'm going to feel like when I wake up" and trying to make sense of fluctuations, which are shrouded in uncertainty ( "It's not clear enough whether I'm fighting something off...or my body's fighting itself" ) and at this stage patients avoid medical help: "It might go away" . Dealing with RA in the foreground: Involves an attempt to regain control of RA through crisis management: "I just try anything" and social withdrawal ( "hibernation mode" ). Some patients will spend a long time trying to manage alone before seeking help. However, patients feel they have lost control of their RA when they are no longer able to manage, when the pain becomes too intense and when the flare has gone on longer than expected ( "It's like a Game-Over" ) and will consider seeking help at this point: "I was in agony and I couldn't do anything" Conclusions: Patients experience life with RA as a continually fluctuating balance between living with their RA in the background and dealing with it in the foreground. Clinicians can use the Fluctuating Balances model as a tool to inform treatment discussions and to improve understanding of life with RA. Disclosure of Interest: None Declared